2021
DOI: 10.1021/acs.biochem.1c00043
|View full text |Cite
|
Sign up to set email alerts
|

First Tandem Repeat of a Potassium Channel KCNN4 Minisatellite Folds into a V-Loop G-Quadruplex Structure

Abstract: The KCNN4 gene encoding a potassium channel protein whose expression has been correlated with tumor progression was found to comprise a guanine-rich minisatellite region with the ability to form a putative G-quadruplex (G4). Given the suggested regulatory role of G4s in gene expression, Gquadruplex formation for the polymorphic first repeat of the minisatellite was studied by nuclear magnetic resonance spectroscopy. A stable G-quadruplex of a truncated mutant sequence was shown to represent one of several coex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…An interesting observation concerns the accommodation of an additional 5’‐flanking sequence. Various studies on the latter reported inconclusive results and no detailed structural study has been performed [27,28,32] . The observation of nicely resolved imino resonances in the ODN2 : C‐ODN2‐Ov design suggests its expanded versatility and makes it amenable for a more detailed structural characterization.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An interesting observation concerns the accommodation of an additional 5’‐flanking sequence. Various studies on the latter reported inconclusive results and no detailed structural study has been performed [27,28,32] . The observation of nicely resolved imino resonances in the ODN2 : C‐ODN2‐Ov design suggests its expanded versatility and makes it amenable for a more detailed structural characterization.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the formation of a parallel G-quadruplex, the vacancy-filling 3'terminal guanosine of the target strand is oriented in an antiparallel fashion and should thus widen the medium groove of the G-quadruplex. On the other hand, ODN2 follows the design of KCNN4 and chl1 sequences, [28,32] which were found to fold into a V-loop G-quadruplex containing a broken first Gcolumn. The first loop bridging a wide groove was cut and the 5'-overhang of the ODN2 elongated to complement the target strand.…”
Section: Design Of Oligonucleotidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, G4s with broken G-columns are far from being mere oddities but outcompete putative canonical topologies in many cases, being of potential significance in the design of G4 structures for various applications. Whereas such structures are heavily promoted by the lack of 5′-flanking residues, the latter were found to still allow folding into a V-loop G4. , Yet, given their noticeable decrease in stability when located in nontruncated sequences, the relevance of V-loop topologies within the genome seems an open question.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas such structures are heavily promoted by the lack of 5′-flanking residues, the latter were found to still allow folding into a V-loop G4. 27,52 Yet, given their noticeable decrease in stability when located in nontruncated sequences, the relevance of V-loop topologies within the genome seems an open question.…”
Section: Journal Of Thementioning
confidence: 99%